2013
DOI: 10.25100/cm.v44i1.1039
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants associated with addictive behavior in Colombian addicted and non-addicted to heroin or cocaine

Abstract: Objective: Determine the prevalence and compare some genetic markers involved in addictive behavior in agroup of addicts to derivative of coca (cocaine/crack) or heroin and a control group of non-addicted peoplematched for gender, age and ethnicity. Methods: A 120 addicts and 120 non-addicts Colombian male were surveyed and genotyped for 18 polymorphismof the OPRM1, DRD2, DRD4, SLC6A3, SLC6A4, ABCB1, DβH and CYP2B6 genes. For the identificationof alleles markers were used mini-sequencing and fragment multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…However, their study showed a strong association between other SNPs in the DβH gene (rs2073837 and rs1611131) when the three groups (healthy control, non-opioid-dependent, and opioid-dependent groups) [32] were compared indicating that the type of gene plays a significant role in establishing any associations. Another study by Isaza et al [27] involving the Columbian population showed no significant association between the DβH polymorphism and drug addiction which also supported our findings of lack of association between DβH rs1611115 and drug addiction. As for the SLC6A3 rs27072 gene, there was a significant difference at the genotypic level (χ 2 = 7.006, p = 0.030) when the drug dependence was compared with the control group.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, their study showed a strong association between other SNPs in the DβH gene (rs2073837 and rs1611131) when the three groups (healthy control, non-opioid-dependent, and opioid-dependent groups) [32] were compared indicating that the type of gene plays a significant role in establishing any associations. Another study by Isaza et al [27] involving the Columbian population showed no significant association between the DβH polymorphism and drug addiction which also supported our findings of lack of association between DβH rs1611115 and drug addiction. As for the SLC6A3 rs27072 gene, there was a significant difference at the genotypic level (χ 2 = 7.006, p = 0.030) when the drug dependence was compared with the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings support the results of the previous study which relate the SLC6A3 gene with drug dependence. SLC6A3 polymorphism is more common in the drug dependence group as compared to the control group [27] which may be influenced by ethnicity. A higher frequency of T alleles (28%) was recorded in the Han Chinese population, which was slightly higher than that reported for the Caucasian (18-19%) polymorphism is lower in Caucasians as compared to the Asian community [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the MTHFR C677T polymorphism has been associated with depression in the context of traumatic stress in early life (Lok et al, 2013), again pointing to genetic and epigenetic determinants of stress-induced negative affect. Another genetic study on Colombian population indicated an association between a polymorphism of the SLC6A3 gene, which encodes the DA transporter or DAT, and addiction to heroin or cocaine (Isaza et al, 2013). Similarly, the same polymorphism was found to be correlated with cocaine dependence in a Brazilian sample ( n = 699) (Guindalini et al, 2006).…”
Section: Latin American Non-clinical Studies and Translational Effortsmentioning
confidence: 99%
“…It should be noted that the same single nucleotide polymorphism in ABCB1 genes was found in Colombian patients with addictive behavior and addicted to heroin and cocaine. Then, it seems viable that genetics may contribute to the high frequency of tramadol use in patients with OAD [ 21 ].…”
Section: Discussionmentioning
confidence: 99%